TINJAUAN ASPEK KEAMANAN DAN KERAHASIAAN BERKAS REKAM MEDIS DI RUANG PENYIMPANAN REKAM MEDIS RUMAH SAKIT "X" JAKARTA TIMUR - Hudiyati Agustini; Erma Febriyani, (MEDICORDHIF Jurnal Rekam Medis, 2021)
ABSTRACT Security is a method of securing information against unauthorized change access. Confidentiality is a limitation for disclosing certain personal information. Based on preliminary observations, it was found that the medical record storage room of the "X" Hospital was not protected and confidential. The door storage room was not locked so that officers other than medical records could enter, it was found that the patient brought his own medical record without being accompanied by a medical record officer, and there were damaged medical records. The result of this research is that security and confidentiality policies and standard operating procedures already exist, but have not been maximally implemented. Security and confidentiality aspects of medical records have not been properly maintained. Judging from the intrinsic factor there are still folders that have not used plastic coated material. From the extrinsic factors there are medical record doors that have not used an access code and always open, and there are damage to medical record files due to rats and cockroaches. it is advisable to reaffirm and socialize the provisions set out in the policy and standard operating procedures to carry out activities in accordance with applicable regulations. Keywords: Security and confidentiality; stronge space; medical record